2014
DOI: 10.1002/jsfa.6998
|View full text |Cite
|
Sign up to set email alerts
|

Phytase in non‐ruminant animal nutrition: a critical review on phytase activities in the gastrointestinal tract and influencing factors

Abstract: This review focuses on phytase functionality in the digestive tract of farmed non-ruminant animals and the factors influencing in vivo phytase enzyme activity. In pigs, feed phytase is mainly active in the stomach and upper part of the small intestine, and added phytase activity is not recovered in the ileum. In poultry, feed phytase activities are mainly found in the upper part of the digestive tract, including the crop, proventriculus and gizzard. For fish with a stomach, phytase activities are mainly in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
299
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(360 citation statements)
references
References 94 publications
(237 reference statements)
11
299
0
11
Order By: Relevance
“…Such precipitates are difficult to solubilize due to phytate's chelating activity and the formation of inaccessible complexes with metal cations, amino acids, peptides and various mineral soil components [13]. The phytate-peptide complexes are at least partially resistant to proteolytic degradation in gastrointestinal tract of non-ruminant animals [14], which prevents extraction of these valuable nutritional factors from plant seeds. Hence, phytate is often considered an anti-nutritional factor for animals.…”
Section: Introductionmentioning
confidence: 99%
“…Such precipitates are difficult to solubilize due to phytate's chelating activity and the formation of inaccessible complexes with metal cations, amino acids, peptides and various mineral soil components [13]. The phytate-peptide complexes are at least partially resistant to proteolytic degradation in gastrointestinal tract of non-ruminant animals [14], which prevents extraction of these valuable nutritional factors from plant seeds. Hence, phytate is often considered an anti-nutritional factor for animals.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism could explain the STA levels in diets with and without the phytase enzyme, because several reports showed that phytase increases protein and AA ileal digestibility (Selle & Ravindran, 2008;Gilani et al, 2012;Selle et al, 2012;Dersjant-Li et al, 2015). Additionally, this could increase the hydrolysis of the endogenous CCK-releasing peptide factors by diminishing their stimuli on the pancreas, even if this has not been reflected in AA ileal digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a better enzyme : substrate ratio could be attained in the SBM diet compared with the SM diet, which allowed the enzyme to release a higher amount of P. Another possible explanation is that phytase activity varies between SM and SBM because of differences in the composition, level, and location of phytate (Dersjant-Li et al, 2015). SM contains more fibre than SBM, and its phytic acid could be closely linked to fibre (Selle & Ravindran, 2008), which could hinder phytase efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Masalah utama yang dialami oleh peternak ayam adalah biaya produksi yang sangat tinggi yang disebabkan oleh mahalnya harga pakan (Kumar et al, 2012). Biaya produksi yang cukup tinggi ini menjadi makin mahal disebabkan oleh sebagian besar pakan yang diberikan kepada ternak belum efisien dicerna oleh ternak ayam (Dersjant-Li et al, 2015). Hal ini disebabkan oleh bahan utama pakan sebagian besar berupa biji-bijian yang mengandung fitat.…”
Section: Pendahuluanunclassified